THE STUDY OF FURNITURE DESIGN (LAY OUT AND ERGONOMIC) DURING THE COVID-19 PANDEMIC AT DKI JAKARTA PUBLIC SERVICE MALL - ATMADI, TUNJUNG (Innovare Journal of Social Sciences, 2023)
The problem currently faced is that changes in interior design styles during the COVID-19 pandemic have greatly affected the furniture design trend. With the current epidemic, we live in isolation that limits social interactions. We need to adapt to carry out daily activities, both indoors and outdoors. We do this so that we avoid exposure to the coronavirus. In this regard, the trend of furniture design inevitably has to change according to health protocols. DKI Jakarta Public Service Mall is one of the things that must improve with this. Public facilities, which are elements in the form of seats, have an important role in public service activities. Public furniture such as seats is an important thing whose function is to support comfort. The purpose of this research is to examine the layout and ergonomics. The research method used in this research study is a qualitative descriptive method, with layout analysis in the waiting room and human dimension analysis as well as posture analysis using the REBA method. The expected benefits in this research are the publication of the results of research and development through a National Journal accredited by Sinta, can achieve the expected Technology Readiness Level and convey the results of research to the Research Center of Mercu Buana University.